Environmental justice lens as a necessity and an opportunity in relocation: The case of the Noordwaard and the Eferding Basin - Chloé ten Brink; Idowu Ajibade; Caroline Zickgraf (Climate Risk Management)
Environmental relocation presents a form of risk management that requires organized movement of communities but are complex to carry out and can have inequitable results. A careful examination of the ethical dimensions of relocation from planning to implementation to outcomes offers an avenue for understanding and addressing potential injustices. Using a deductive environmental justice framework, we analyzed two compensation-based relocations, also understood as buyouts: the 2013 Danube flood relocation in Austria’s Eferding Basin and the Noordwaard de-poldering in the Netherlands’ Room for the River program. We combined document analysis (n = 62) and semi-structured interviews (n = 20) to assess justice concerns, focusing on distributive, procedural, and ecological dimensions. Distributive justice was primarily addressed through financial compensation, offering 100 % market value in the Noordwaard and 80 % in the Eferding Basin, but non-monetary considerations were relatively neglected. Procedural justice, particularly transparency and citizen participation, were insufficient. Considerations of ecological justice were absent in the Eferding Basin but the Noordwaard’s use of nature-based solutions and prioritization of spatial quality led to multiple environmental benefits. Overall, this paper argues that justice should not be viewed simply as a criterion to be fulfilled, but rather as a guiding principle for addressing the broader, short and long-term impacts, and well-being related to relocation. By adopting this perspective, justice can be understood as an opportunity for positive transformation, allowing environmental relocation to be framed as a process with the potential for meaningful, beneficial change rather than solely a response to current or future flood risk.